Memaknai Hospitalitas di Era New Normal: Sebuah Tinjauan Teologis Lukas 10:25-37 - Gunawan Yuli Agung Suprabowo (HARVESTER: Jurnal Teologi dan Kepemimpinan Kristen, 2020)
Abstract : Hospitality in the new normal era has brought new problems because the actions of hospitality towards other people are at risk of corona virus. Therefore the construction of hospitality needs to be reformulated amid a changing context. This was done through a study of the text of Luke 10: 25-37 with the historical critical method. From the results of the study is found several theological points. First, hospitality must be based on compassion which will enable a person to empathize for  strangers although faced with a difficult situation. Second, acts of hospitality need to be done collaboratively across groups, ethnicity and religions facing of an increase in the communities affected by Covid-19. Third, the construction of hospitality need to be done with a digital technology media approach that functions intertwined with human interaction and is beneficial in presenting the hospitality of God to anyone penetrating geographical boundaries.Keywords: hospitality, compassion, collaborative, digital technology. Abstrak: Hospitalitas di era new normal telah membawa persoalan baru karena tindakan hospitalitas terhadap orang lain menjadi beresiko pada penularan virus corona. Karenanya konstruksi hospitalitas perlu dirumuskan kembali di tengah konteks yang sudah berubah. Hal itu dilakukan melalui penelitian teks Lukas 10:25-37 dengan metode historis kritis. Dari hasil penelitian ditemukan beberapa pokok teologis. Pertama, hospitalitas harus berpijak pada belas kasih yang akan memampukan seseorang untuk berempati terhadap orang asing walau diperhadapkan pada situasi yang sulit. Kedua, tindakan hospitalitas perlu dilakukan secara kolaboratif lintas kelompok, etnik, dan agama dalam menghadapi meningkatnya masyarakat yang terdampak Covid-19. Ketiga, konstruksi hospitalitas perlu dilakukan dengan pendekatan media tehnologi digital yang berfungsi terjalinnya interaksi antar manusia dan bermanfaat dalam menghadirkan keramahtamahan Allah pada siapapun menembus batas-batas geografis.Kata kunci: hospitalitas, belas kasih, kolaboratif, tehnologi digital.